In-vivo analysis of sternal angle, sternal and sternocostal kinematics in supine humans during breathing. (7th November 2017) - Beyer, Benoît; Feipel, Véronique; Sholukha, Victor; Chèze, Laurence; Van Sint Jan, Serge
Abstract: This paper aims at contributing to the understanding of the combination of in vivo sternum displacement, sternal angle variations and sternocostal joints (SCJ) kinematics of the seven first rib pairs over the inspiratory capacity (IC). Retrospective codified spiral-CT data obtained at total lung capacity (TLC), middle of inspiratory capacity (MIC) and at functional residual capacity (FRC) were used to compute kinematic parameters of the bones and joints of interest in a sample of 12 asymptomatic subjects. 3D models of rib, thoracic vertebra, manubrium and sternum were processed to determine anatomical landmarks (ALs) on each bone. These ALs were used to create local coordinate system and compute spatial transformation of ribs and manubrium relative to sternum, and sternum relative to thoracic vertebra. The rib angular displacements and associated orientation of rotation axes and joint pivot points (JPP), the sternal angle variations and the associated displacement of the sternum relative to vertebra were computed between each breathing pose at the three lung volumes. Results can be summarized as following: (1) sternum cephalic displacement ranged between 17.8 and 19.2 mm over the IC; (2) the sternal angle showed a mean variation of 4.4° ± 2.7° over the IC; (3) ranges of rib rotation relative to sternum decreased gradually with increasing rib level; (4) axes of rotation were similarly oriented at each SCJ; (5) JPP spatial displacements showed less variations at first SCJ compared to levels underneath; (6) linear relation was demonstrated between SCJ ROMs and sternum cephalic displacement over the IC.